Inhibition of Heme Oxygenase-1 Enhanced Antitumor Effect of Gemcitabine in Cholangiocarcinoma - Kongpetch, Sarinya (Srinagarind Medical Journal, 2013)
Background and objective: Heme oxygenase-1 (HO-1) is a key enzyme exerting potent cytoprotection, cell proliferation especially the resistance to anticancer agents. This study aimed to investigate the roles of HO-1 in human cholangiocarcinoma (CCA) cells, whether inhibit HO-1 could increase the cytotoxic effect of gemcitabine (Gem) in CCA cell in vitro and in vivo using mice bearing CCA tumor-xenograft. Methods: The cytoprotective role of HO-1 in CCA cell (KKU-100) was assessed by using HO-1 inhibitor (ZnPP). The cytotoxic effects of combinations of Gem with ZnPP were assayed by fluorescence dye staining (AO/EB). Western blot analysis determined p21, cytochrome c with using b-actin as loading control. In vivo study; nude mice bearing KKU-100 xenograft were treated with combination of Gem and ZnPP. Mice tissues were performed immunohistochemistry for p21, p53 and mdm2. Results: Inhibition of HO-1 by zinc protoporphyrin IX (ZnPP) sensitized KKU-100 to the cytotoxicity of Gem. The combination of ZnPP and Gem triggered protein related apoptosis and suppress-growth by enhancing the release of cytochrome c, and increased p21Cip/WAF1 levels, compared to both treatments alone. In vivo, ZnPP significantly potentiated the effects of GEM to suppress tumor-growth. From immunohistochemistry, the tumor suppressor protein; p53 and p21 were highly expressed in the combination group where mdm2 expression was not detected. Conclusions: Inhibition of HO-1 potentiated antitumor effect of Gem in CCA tumor. Targeted inhibition of HO-1 may be a strategy to overcome drug resistance in chemotherapy of bile duct cancer. Key word: Heme oxygenase-1, cholangiocarcinoma and gemcitabine